Pelatihan Dan Pendampingan Digital Marketing Untuk Peningkatan Brand Awareness UMKM “Dapoer Kerontang” - Rahayu Musfirah; Ika Korika Swasti (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Low competitiveness is generally caused by the limited ability of business actors to carry out marketing. So the purpose of this service is to increase the knowledge of MSMEs actors about the importance of digital media for marketing and also to build product identity through training and mentoring. The partner in this activity is the MSMEs Dapoer Kerontang located in Rungkut Mejoyo, Surabaya. The training provided is Digital Marketing socialization by creating an Instagram social media account, registration of point of sale locations on Gmaps, Product Photos, Logo and Packaging Design, and Product Catalogs. The results obtained from this community service activity are that Dapoer Kerontang MSMEs products provide knowledge to Dapoer Kerontang MSMEs owners regarding the importance of marketing their products through digital media. after the training and mentoring are expected to increase Brand Awareness, have a wider market, increase the competitiveness of MSMEs through the use of digital marketing, and provide knowledge to Dapoer Kerontang MSMEs owners regarding the importance of marketing their products through digital media.